Agile AI-Quality Management Concerning LEAN Solutions from a Strategic Perspective (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
The paper describes the research work about the strategic imperative for agile quality management systems in medical engineering companies in Austrian, Germany, and Switzerland until 2030. The industry operates in a volatile, uncertain, complex, and ambiguous (VUCA) environment, where the advantage of agility is expressed in an Agile Performance Index. Although, current developments of artificial intelligence (AI) need to be factored in. The goal of the research work is to answer a research question about how the strategic imperative can be determined by taking AI into account. Literature review and applying a qualitative research approach with nine expert interviews unveiled four main dimensions: (1) societal impact, (2) operational compatibility, (3) data quality, and (4) model performance. It solicits new approaches for resilient processes. Further, it enables the decision makers to keep the long-term ramifications in mind by leveraging attractive spot business. The result of the research is explained with a SWOT analysis, which contains nine distinct different strategies to tackle the challenges in an VUCA environment for medical engineering companies.